Exploring para teacher’s strategies in developing pupil’s phonemic awareness in New Normal - Cerna, Glory Mei Sabandal (SAINTIS Publishing, 2022)
This study examines the applied strategies of para teacher in developing the English language phonemic awareness of a first grader in the context of modular distance learning delivery modality. To develop such awareness, students should be able to master the tasks such as (1) phoneme isolation, (2) phoneme identity (3) phoneme deletion, (4) phoneme segmentation, (5) phoneme categorization, and (6) phoneme blending. This study concentrates on how the para teacher addresses all the six components of phonemic awareness and explores whether there are any additional elements that should be considered with English learners’ phonemic awareness development. In this case study, data were collected through semi-structured interviews, field notes from modular instruction observation, and phonemic awareness assessment results. The results from this case study imply that systematic teaching strategies are essential to consider with English learners’ phonemic awareness development. The findings of this study also disclosed that both para teacher and learner’s motivation is an essential component in teaching and learning phonemic awareness.